Lower abdominal pain as a problem in child gynecology - G. Jarząbek-Bielecka; M. Mizgier; M. Chuchracki; M. Pisarska-Krawczyk; E. Jakubek; W. Kędzia (IMR Press, 2020)
Lower abdominal pain in a girl is a common problem in gynecology of the developmental age (10-20%). It corresponds to the criteria of the concept of "chronic pelvic pain" (CPP), which is defined in accordance with the American College of Obstetricians and Gynecologists (ACOG) as chronic, non-cyclical pain in the area of the lower abdomen, unrelated to the menstrual cycle, lasting at least three months, or cyclic pain lasting for six months. The overriding aim of treatment of CPP in girls and young women is to alleviate existing pain, prevent recurrence of chronic symptoms, ensure future reproductive functions, and restore proper functioning and improve quality of life.